2007
DOI: 10.1159/000102175
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation at the Fetomaternal Interface in Hemomonochorial Placentae from Five Widely Separated Species of Mammal: Is There Evidence for Convergent Evolution?

Abstract: Hemomonochorial placentation occurs in diverse species. We have examined placental glycosylation in five widely separated mammals with this type of placentation – lesser hedgehog tenrec (Echinops telfairi), spotted hyena (Crocuta crocuta), nine-banded armadillo (Dasypus novemcinctus), human (Homo sapiens) and guinea pig (Cavia porcellus) – in order to assess whether evolutionary convergence to the hemomonochorial state is accompanied by a similar convergence of glycan expression. Placentae from 2 E. telfairi, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 79 publications
4
29
0
1
Order By: Relevance
“…Siglec-6 immunolocalises to the syncytial MVM in human term placenta [50]. Though lectin histochemistry has suggested that human term placenta has rather low levels of terminal α2,6-linked sialic acid, showing more α2,3-linkages [51], trophoblast (including the extravillous population) does contain glycoproteins with siglec-6 recognition capacity. Siglec-6 also binds leptin [50]; thus, the siglec-6 binding site in villous trophoblast may be occupied by cis-ligands.…”
Section: Glycan-based Adhesionmentioning
confidence: 99%
“…Siglec-6 immunolocalises to the syncytial MVM in human term placenta [50]. Though lectin histochemistry has suggested that human term placenta has rather low levels of terminal α2,6-linked sialic acid, showing more α2,3-linkages [51], trophoblast (including the extravillous population) does contain glycoproteins with siglec-6 recognition capacity. Siglec-6 also binds leptin [50]; thus, the siglec-6 binding site in villous trophoblast may be occupied by cis-ligands.…”
Section: Glycan-based Adhesionmentioning
confidence: 99%
“…The presence of Siglec-6 at the syncytial surface suggests the possibility that cis-interactions with sialylated ligands in the trophoblast may contribute to plasma membrane organisation [46]. There appears to be convergent evolution of glycosylation at this tissue-blood interface [47]. Five widely separated species of mammal with hemochorial placentation (lesser hedgehog tenrec Echinops telfairi, spotted hyena Crocuta crocuta, nine-banded armadillo Dasypus novemcinctus, human Homo sapiens and guinea pig Cavia porcellus) have marked similarities in glycosylation of the trophoblast apical/microvillous membrane.…”
Section: Hemochorial Placentationmentioning
confidence: 99%
“…The inner trophoblast layer exhibited an increase in non-bisected bi/tri-antennary complex N-glycan (PSA) as well as N-acetyl galactosamine (SBA) and glucosamine oligomers (WGA) with maturity, but other changes were of a minor degree. Sialic acid in a2,3-linkage, bound by MAA, was not found in the trophoblast at any stage, which is unusual for haemochorial placentae [23], while fucosyl residues in a1,2-linkage were also weak or absent, as shown by the lack of binding of LTA and UEA-1. The difference in glycosylation between the two microvillous surfaces may reflect altered functional requirements.…”
Section: Fig 5 a And Bmentioning
confidence: 77%
“…Non-osmicated plastic embedded specimens were sectioned at 0.75 mm and stained with a panel of 24 biotinylated lectins, followed by an avidin-peroxidase revealing system as previously described [22,23]. Sections were assessed using a semiquantitative ranking system where staining intensity was allocated a grade from 0 (negative) to 4 (intense staining).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation